CHILD FEEDING PRACTICE, SANITATION HYGIENE, AND OTHER FACTORS OF DIARRHEA IN CHILDREN AGED 6-23 MONTHS IN INDONESIA: ANALYSIS OF IDHS 2017 - Salma Luthfiyah Sani; Endang Laksminingsih Achadi (Universitas Airlangga, 2023)
Diarrhea remains one of the major contributors of under five children mortality worldwide. IDHS 2017 data show that 6-23 month-old children have the highest diarrhea prevalence. The objective of this research is to analyze the association of child feeding practices (early initiation of breastfeeding, continued breastfeeding, bottle feeding, MDD, MMF, MAD); sanitation hygiene (source of drinking water, treatment of drinking water, toilet facility, handwashing facility); healthcare utilization factors (immunization status, vitamin A in the last 6 months); and socio-demographic factors (maternal age, maternal education, maternal working status, economic status, residence) with diarrhea incidence in 6-23 month-old children in Indonesia. This cross-sectional study included a total of 4,030 children aged 6-23 months from IDHS 2017. Chi-square test and multiple logistic regression were applied to analyze factors associated with diarrhea. It was found that the prevalence of diarrhea was 19.8% in 2017. Bivariate analysis shows that diarrhea was significantly associated with continued breastfeeding, bottle feeding, toilet facility, source of drinking water, maternal age, economic status, and place of residence. Furthermore, multivariate analysis results in some variables have a statistically significant association with diarrhea, which are the use of bottle feeding, non-improved toilet facility, maternal age 15-29 years, and low maternal education. The dominant factor associated with diarrhea was toilet facility (OR=1.500, 95% CI 1.262-1.784). Healthy latrines utilization, cleaning baby bottle properly, and enhancing health education for mothers are pivotal to prevent diarrhea and maintain children’s health at 6-23 months.